New taxa of the mite family Neopygmephoridae (Acari: Heterostigmata) from alpine New Zealand - Khaustov, Alexander A.; Minor, Maria A. (Zootaxa, 2018)
Two new genera and four new species of the mite family Neopygmephoridae (Acari: Pygmephoroidea) are described from the alpine zone (1600–1900 m a.s.l.) of the Central Otago region of the South Island of New Zealand: Protobakerdania Khaustov and Minor gen. nov. with the type species Pygmephorus togatus Willmann, 1942, Neobakerdania Khaustov and Minor gen. nov. with the type species Neobakerdania pilosa Khaustov and Minor sp. nov., and the species Protobakerdania diseta Khaustov and Minor sp. nov., Troxodania minuta Khaustov and Minor sp. nov., and Bakerdania alpina Khaustov and Minor sp. nov. Eight species are moved to Protobakerdania Khaustov and Minor gen. nov. from Bakerdania Sasa, 1961: P. aperta (Rack and Kaliszewski, 1985) comb. nov., P. arvorum (Jacot, 1936) comb. nov., P. arvorum nodulosa (Mahunka, 1969b) comb. nov., P. baloghi (Mahunka, 1969b) comb. nov., P. crenata (Mahunka, 1969b) comb. nov., P. pristinus (Mahunka, 1968) comb. nov., P. randae (Sevastianov and Zahida Al Douri, 1989) comb. nov., and P. togatus (Willmann, 1942) comb. nov.